THE ROLE AND ROLE OF ASTRONOMY LABORATORY TEACHERS IN THE TRAINING OF HIGHLY QUALIFIED TEACHERS IN PEDAGOGICAL HIGHER EDUCATION INSTITUTIONS - G. I. Sayfullaeva; E. A. Qudratov; S. X. Mirzakandova (Galaxy International Interdisciplinary Research Journal, 2021)
This article describes the role of laboratory work in the training of highly qualified teachers of astronomy in pedagogical higher education institutions.